2006
DOI: 10.1016/j.jhsb.2006.03.165
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Carpal Tunnel Surgery with Respect to Age

Abstract: Six hundred and thirty five carpal tunnel decompressions in 490 patients were studied prospectively in two hand surgery centres to assess the effect of increasing age on the outcome after surgery. The outcome was assessed using the Levine-Katz carpal tunnel questionnaire, Tinel's sign, Phalen's test, Semmes-Weinstein monofilaments and pinch and grip strengths. Assessments were made pre-operatively, at 2 weeks and 6 months postoperatively. Information was also sought concerning co-morbid conditions. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
(15 reference statements)
2
16
1
Order By: Relevance
“…2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no objective explanation has been suggested for these observations. As the symptoms for carpal tunnel syndrome include wrist pain, paresthesia and weakness in grip strengths, a number of medical conditions can produce a similar clinical picture; therefore, as standard practice, our department investigates these patients with neurophysiology before a surgical treatment strategy is considered if conservative treatment is unsatisfactory.…”
mentioning
confidence: 95%
“…2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no objective explanation has been suggested for these observations. As the symptoms for carpal tunnel syndrome include wrist pain, paresthesia and weakness in grip strengths, a number of medical conditions can produce a similar clinical picture; therefore, as standard practice, our department investigates these patients with neurophysiology before a surgical treatment strategy is considered if conservative treatment is unsatisfactory.…”
mentioning
confidence: 95%
“…4,15,20,24,31 Although its purview is restricted to symptoms and function of the hand, its questions do not exclusively examine functions of the median nerve and thus it may be a valid instrument for measuring outcomes after ulnar nerve decompression. Validation of one or more of these self-reported outcome instruments will allow meaningful comparisons of the various treatments for UNE.…”
mentioning
confidence: 99%
“…The LK scores were the basis for the matching because previous studies demonstrated that these scores were the strongest determinants in the change in scores following surgery. Age, gender, BMI, and duration of symptoms had little effect on change in LK scores (Bodavula et al, 2007;Burke et al, 2006;Wilgis et al, 2006). For each non-surgical patient who completed the questionnaire, a match was made with two alternative matches.…”
Section: Methodsmentioning
confidence: 99%